# Solve log_{11}(y + 8) + log_{11}4 = log_{11}60

**Solution:**

Given expression is

log_{11}(y + 8) + log_{11}4 = log_{11}60.

Log_{a}xy = log_{a}x + log_{a}y

Therefore we can state:

log_{11}(y + 8) + log_{11}4 = log_{11}[(y + 8) × 4]

Since log_{11}(y + 8) + log_{11}4 = log_{11}60,

log_{11}4(y + 8) = log_{11 }60

Which implies

4(y + 8) = 60

y + 8 = 60/4

y + 8 = 15

y = 15 - 8

y = 7

## Solve log_{11}(y + 8) + log_{11}4 = log_{11}60

**Summary:**

Solving log_{11}(y + 8) + log_{11}4 = log_{11}60, we obtain y = 7

Math worksheets and

visual curriculum

visual curriculum